Perfectionism and performance in a trail running competition: a prospective study of the interactive effects of perfectionism - Walerianczyk, W. (Journal of Sports Sciences, 2023)
Several studies explored the links between perfectionism and sport performance. However, only a few studies examined this relationship in the context of real sport competition and with a focus on the possible interactive effects of the dimensions of perfectionism. The present study aimed to investigate whether the two higher-order dimensions of perfectionism - perfectionistic strivings and perfectionistic concerns - interact in predicting performance in mountain trail running competitions. 167 athletes (54 females, 113 males) aged 19 to 65 (M = 39.32, SD = 9.35) completed measures of perfectionism in the week prior to the competition. Regression analyses revealed that perfectionistic strivings were a positive predictor of the runners` performance while perfectionistic concerns showed no significant associations with performance. However, a more in-depth exploration within the framework of the 2 × 2 model of perfectionism showed that the beneficial effects of high perfectionistic strivings are no longer significant when accompanied by high levels of perfectionistic concerns. These results support the notion that perfectionistic concerns may be detrimental to sport performance even if their overall, direct effects are not significant, adding first evidence of the existence of standard but also flipped perfectionistic tipping points in the context of sport performance.